2007
DOI: 10.1158/0008-5472.can-07-0931
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol-Induced Apoptosis in Human Lung Carcinoma Cells Is Coupled to the Endoplasmic Reticulum Stress Response

Abstract: Farnesol (FOH) and other isoprenoid alcohols induce apoptosis in various carcinoma cells and inhibit tumorigenesis in several in vivo models. However, the mechanisms by which they mediate their effects are not yet fully understood. In this study, we show that FOH is an effective inducer of apoptosis in several lung carcinoma cells, including H460. This induction is associated with activation of several caspases and cleavage of poly(ADP-ribose) polymerase (PARP). To obtain insight into the mechanism involved in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 49 publications
(94 reference statements)
7
109
1
4
Order By: Relevance
“…S5). Because other proapoptotic genes detected in our study are also often activated during ESR (39), the data suggest that STAT3 ND suppression may be especially important for STAT3 functions under conditions of ESR in cancer cells. The identification of differences in epigenetic mechanisms that underlie differential activity of the STAT3 ND in normal and cancer cells can offer novel potential therapeutic targets for cancer treatment.…”
Section: St3-h2a2mentioning
confidence: 58%
“…S5). Because other proapoptotic genes detected in our study are also often activated during ESR (39), the data suggest that STAT3 ND suppression may be especially important for STAT3 functions under conditions of ESR in cancer cells. The identification of differences in epigenetic mechanisms that underlie differential activity of the STAT3 ND in normal and cancer cells can offer novel potential therapeutic targets for cancer treatment.…”
Section: St3-h2a2mentioning
confidence: 58%
“…A significant fraction of the mRNA species (33%) identified in the initial A549 screen were modulated in the same manner by the combination of pazopanib and lapatinib (but not by other chemotherapeutic agents such as cisplatin, or drug combinations; data not shown) in all the cell lines (Figure 5c; Supplementary Table S3), suggesting that pazopanib and lapatinib might exert synergistic effects on multiple different malignancies. Among the 58 genes that were induced specifically by the combination regimen in all cell lines, several have previously been involved in apoptotic signaling, in particular p53 (Pietsch et al, 2008), PHLDA1 (also known as T-cell-death-associated gene 51, TDAG51) (Hayashida et al, 2006;Joo et al, 2007;Oberst et al, 2008) and RHOT1 (ras homolog gene family, member T1; also known as mitochondrial Rho; Miro1) (Fransson et al, 2003). Indeed, we observed that the combination of pazopanib and lapatinib was able to kill the five carcinoma cell lines included in the transcriptome analysis, as well as ovarian (SKOV3) and cervix cancer cells (HeLa), yielding highly significant synergistic effects of both compounds as compared to each of them alone (Figure 5d; Supplementary Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…[31][32][33] To date activation of one or more branches of the UPR has been reported in oesophageal adenocarcinomas, 34 breast, [35][36][37] gastric 38 and lung cancers. 39 Tumour cells have an important interaction with the cellular context in which they are Targeting the UPR in cancer found including dependence on fundamental limiting factors such as hypoxia, 40 lack of nutrients and acidosis. These factors can be partially overcome if the tumour is able to establish a blood supply via secretion of pro-angiogenic factors.…”
mentioning
confidence: 99%